Creación de la ruta turística sostenible Ruta del Banano para el desarrollo Agroturístico de la ciudad de Quevedo, año 2019 - Barragan Veloz, Roxana Elizabeth (2020)
In a world with an increasingly competitive and globalized economy where macro companies, including large tour operators, dominate most of the markets for goods and services, it is necessary to promote the creation of other types of inclusive and sustainable ventures that accommodate to all the actors of the communities and in this way the benefits of the tourist activity are distributed more equitably. A tourist route follows an itinerary with several sites of tourist interest. The term tourist circuit is more frequently associated with a loop, while a route usually has different points: initial and final. However, these terms are not limited exclusively to these definitions. In Ecuador, the development of tourist destinations in the context of today has covered an important space as an alternative to counteract the lack of sources of economic income and thus improve the quality of life of the inhabitants of a country, territory and community. On the other hand, the creation of trails and routes in already discovered tourist places and in places not yet known, the tourist use has contributed in large part to improve the economic situation of the inhabitants of a certain area. Banana is one of the oldest natural fruits in the world and the Ecuadorian State enjoys exceptional climatic conditions for its cultivation. The richness of its land has allowed that, since the end of the 40s, it has had and has an important weight in the development of the country, both economically and socially.